Peningkatan UMKM di Kota Padangsidimpuan Melalui Sektor Pemberdayaan Sumber Daya Manusia - Kapika Annisa; Wardani Gurning (Universitas 45 Surabaya, 2024)
This study aims to analyze efforts to improve the performance of Micro, Small, and Medium Enterprises (MSMEs) in Padangsidimpuan City through empowering Human Resources (HR). The research method used is qualitative with a case study approach. Data were obtained through in-depth interviews with 15 MSME actors and community leaders. The results of the study indicate that empowering HR through entrepreneurship training, increasing digital literacy, and technical skills training can increase business efficiency, product innovation, and MSME competitiveness. This study provides a strengthening of collaboration between the government, educational institutions, and the private sector in supporting HR empowerment programs.